Waste management and resource recovery - Rhyner, Charles; Schwartz, Leander ;Wenger, Robert ;Kohrell, Nary (Florida, United States : CRC Press, 2019)
This book provides a basic understanding of waste management problems and issues faced by modern society. Scientific, technical, and environmental principles are emphasized to illustrate the processes of municipal and industrial solid wastes and liquid wastes, and the nature of impacts resulting from waste dispersal and disposal in the environment. Economic, social, legal, and political aspects of waste management are also addressed.
Waste Management and Resource Conservation -- Waste Generation -- Collection and Transportation of Solid Waste -- Solid Waste Source Reduction and Recycling -- Processing Solid Wastes and Recyclable Materials -- Wastewater Treatment -- Biological Treatment of Waste Solids -- Incineration, Pyrolysis, and Energy Recovery -- Landfilling of Wastes -- Landfill Leachate and Gas Management -- Application of Wastewater and Biosolids to Land -- Hazardous Waste -- Costs and Management of Waste Facilities and Systems.
First published in paperback. | Originally published: 1995.
Includes bibliographical references and index.
Keywords: RECYCLING